EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA POKOK BAHASAN LIMIT FUNGSI DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA (Penelitian Dilaksanakan di SMA - Dwi Winarni; Budiyono Budiyono; Dewi Retno Sari (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objectives of this study were to know: (1) which one gives student better learning achievement, Numbered Heads Together learning process, Think Pair Share one  with Contextual Teaching and Learning, or conventional one, (2) which one having better learning achievement in mathematics, students who have the level of low  anxiety, medium one, or high one, (3) which level of anxiety in learning mathematics gives better learning achievements with Numbered Heads Together learning model, Think Pair Share one with Contextual Teaching and Learning approach one, or conventional one, (4) which learning model (Numbered Heads together, think pair share with contextual Teaching and Learning approach, or conventional) gives better learning achievement  in mathematics  toward the level of low anxiety, medium one , or high one.It was aquasi-experimentalstudy using twoindependent variables(model of learning andthe anxiety of learning mathematics) andonedependent variable(learning achievement of mathematics). The instruments used to collect the data were documentation,testing, andquestionnaires. Two-way ANOVA was used to analyze the data. The sample-taking was done using Sratified Cluster Random Sampling.The results of theresearchare. (1) the learning achievement in Conventional learning model andNumberedHeads Together one areequally well, Think Pair Sharemodelis better thanconventionalone,whileNumberedHeads Togetherandthinkpair share are equally well, (2) the learning achievement in mathematics toward low anxiety and medium one are equally well, low-anxiety learning is better than  highanxiety, medium anxiety and highoneareequally well, (3) in NumberedHeads Together, Think Pair Share, andconventional model, the learning achievement in mathematics toward low anxiety and medium one are equally well, low-anxiety is better than  highanxiety, medium anxiety and highoneareequally well, and (4) the learning achievement inlow, medium, andhigh anxietyat the learning achievement in Conventional learning model andNumberedHeads Together one areequally well, Think Pair Sharemodelis better thanconventionalone,whileNumberedHeads TogetherandThinkPair Share are equally well.   Keywords: Numbered Heads Together, Think Pair Share,Conventional